Hemoperitoneum Due to Dissection and Rupture of the Superior Mesenteric Artery in a Patient With COL3A1 Mutation - Tironi, Fabio; Lakmali, Wijesinghe; Herath, Jayantha (Academic forensic pathology, 2024)
Introduction: Vascular Ehlers-Danlos syndrome (vEDS) is an autosomal dominant disorder that results from mutations in the collagen type III gene. It is a risk factor for medium-sized artery aneurysms, dissections, and ruptures. We report a case of hemoperitoneum due to medial dissection and rupture of the superior mesenteric artery related to vEDS. Methods: A full body CT scan and full three cavity autopsy was performed in a 47-year-old man with a history of an intermittent abdominal cramping for one week rand complex past medical history that included a sigmoid bowel perforation at age 20, and previous popliteal artery pseudoaneurysm rupture. Histology and genetic testing were performed. Results: The postmortem computed tomography and autopsy showed a significant hemoperitoneum due to a ruptured dissection of the superior mesenteric artery and branches, and multiple splanchnic artery dissections with renal and small bowel infarctions. Genetic testing revealed a heterozygous COL3A1 gene variant associated with Ehlers-Danlos syndrome. Death was attributed to hemoperitoneum due to medial dissection and rupture of the superior mesenteric artery due to arteriopathy. Discussion: The relatively young age and medical history correlate with the autopsy findings and genetic testing towards the conclusion of an arteriopathy consistent with vEDS.